Development and Characterization of Bentonite Clay Adsorbents Modified by Amines for the Adsorption of Carbon Dioxide - ELKHALIFAH, ALI ELTAYEB IBRAHIM (2013)
The aim of the present work is to systematically investigate the use of bentonite clay modified by amines for CO2 capture. For this purpose, different alkali and alkaline earth and transition metal cation forms of bentonite were treated with protonated mono-, di- and triethanolamine compounds to prepare different amines modified bentonite adsorbents via ion exchange and d and f coordination mechanisms respectively. The structural characteristics, thermal analysis and surface properties of the synthesized materials as well as the reference material were investigated. CO2 adsorption studies were gravimetrically conducted using Magnetic Suspension Balance (MSB) equipment under different temperature and pressure conditions. The results show that the basal spacings of amines modified bentonite adsorbents have increased with the molar mass of ammonium cations used. The presence of the common IR peaks of amine compounds in the IR spectra of amines modified bentonite clay adsorbents has qualitatively supported the intercalation of ammonium cations in the interlayer space of bentonite. It was also found that the molar mass of amines used has an inverse effect on the amount of the adsorbed water, its desorption temperature and the specific surface area for bentonite clay adsorbents modified by amines. The presence of carbon, hydrogen and nitrogen in bentonite after treatment by amines has quantitatively confirmed the intercalation of amines into the interlayer space of bentonite. Based on CO2 adsorption results, it was found that the CO2 adsorption capacities on all studied bentonite clay adsorbents modified by amines increased between 2.68 to 3.15 mmol/g, compared to 0.93 mmol/g for untreated bentonite. Among the isotherm models used, it was found that Freundlich and Redlich-Peterson models adequately represent the experimental data with higher correlation coefficients (R2) and minimum errors. viii The rate of CO2 adsorption on untreated bentonite and MEA+-Mg-MMT adsorbents was found to be very fast approaching their equilibrium loading capacity within the first period of adsorption process ( 10 mins). The CO2 adsorption thermodynamic study on MEA+-Mg-MMT adsorbent material revealed that the process is physical, spontaneous and exothermic process. The evaluation of CO2 adsorption energy using Dubinin-Radushkevich isotherm model at different temperatures showed that the mean free energies of CO2 adsorption on untreated bentonite and bentonite clay modified by amines were in the range between 2.092 to 2.333 and 2.505 to 3.329 KJ/mol respectively, indicating a physical CO2 adsorption process. The CO2 pure component selectivity over CH4, N2 and O2 on MEA+-Mg-MMT at different temperatures showed that the Henry’s law constants for CO2 were higher among other light gases, indicating higher selectivity of CO2 over CH4 (1.36, 4.85 and 3.43) and CO2 over N2 (13.79, 9.91 and 6.32) at 298, 323 and 348 K respectively, whereas the selectivity of CO2 over O2 were also found to be high (8.69, 7.61 and 4.51) at 323, 348 and 373 K respectively. Based on the regenerability study, it was founf that MEA+-Mg-MMT does not show noticeable deterioration in recurring CO2 adsorption-desorption cycles, indicating its recyclability and stability. Based on the results obtained in the present research work, it can be concluded that the treatment of magnesium form of bentonite clay with monoethanolammonium cations results in the enhancement and improvement of the surface properties as well as the affinity towards CO2 adsorption (0.79 mmol/g, at 298 K and 1 bar) compared to other adsorbents of similar nature.